Yemen : dancing on the heads of snakes - Clark, Victoria, 1961- (Yale University Press, 2010)
"Yemen is the dark horse of the Middle East. Every so often it enters the headlines for one alarming reason or another -- links with al-Qaeda, kidnapped Westerners, explosive population growth -- then sinks into obscurity again. But, as Victoria Clark argues in this riveting book, we ignore Yemen at our peril. The poorest state in the Arab world, it is still dominated by its tribal makeup and has become a perfect breeding ground for insurgent and terrorist movements. Clark returns to the country where she was born to discover a perilously fragile state that deserves more of our understanding and attention. On a series of visits to Yemen between 2004 and 2009, she meets politicians, influential tribesmen, oil workers and jihadists as well as ordinary Yemenis. Untangling Yemen's history before examining the country's role in both al-Qaeda and the wider jihadist movement today, Clark presents a lively, clear, and up-to-date account of a little-known state whose chronic instability is increasingly engaging the general reader"--Publisher description.